Faktor-Faktor Sosiolegal yang Menentukan dalam Penanganan Perkara Korupsi di Pengadilan - M. Syamsudin (Jurnal Hukum IUS QUIA IUSTUM, 2010)
This research discusses sociolegal factors problem which determines the treatment of corruption case in court. The discussed problem focus is sociolegal factors works in treatment of corruption case so that general court recently tends to impose free from charge decision. This research is classified as empirical legal research (non-doctrinal) with sociolegal approach. Data is collected through interview, observation and document study analyzed based on interactive model from Mattew B Miles and A Michael Haberman. Data validation is performed by triangulating source and method. The result of research shows that there are sociolegal factors which work in the treatment of corruption case both in Corruption Court and General Court. Those factors includes: case input quality, availability of eveidence and quality of indictment, composition and qualification of panel of judges amd social environment.Key words : Sociolegal factor, treatment of corruption case, court